From flower to honey - Nelson, Penelope, 1994- (2021)
"In From Flower to Honey, early fluent readers learn how honey is made, from bees collecting flower nectar to beekeepers collecting and jarring it. Vibrant, full-color photos and carefully leveled text will engage young readers as they learn about how this food gets to their tables. An infographic illustrates the cycle with real photos and descriptions. From Flower to Honey also features reading tips for teachers and parents, a table of contents, a glossary, and an index"--
"Bullfrog Books are published by Jump!"
Includes index.
Ages 5-8.
Grades K-1.
Keywords: Honey -- Juvenile literature; Bee culture -- Juvenile literature; Honeybee -- Juvenile literature